PLANT GENETIC RESOURCES IN KAZAKHSTAN: STATE AND PROSPECTS - B. Alimgazinova; M. Yessimbekova (Вавиловский журнал генетики и селекции)
Conservation of the biodiversity of crops and their relatives is considered with regard to agriculture. Attention is focused on the collection, study, storage, and documentation for better use, diversification, and meeting new requirements of agriculture, food industry, and climate. Conservation of biodiversity is viewed as a multifaceted field of research.